2020
DOI: 10.1007/s12603-020-1311-x
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Multimorbidity in Older Adult Inpatients in China

Abstract: Research on multimorbidity of older adults in China is still at the early stage. For the community-dwelling older population, a cross-sectional community health survey in southern China showed that the average number of chronic conditions was 1.68 ±1.60, and the prevalence of multimorbidity was reported to be 45.5% (11). Meanwhile, a study from northeastern China reported that almost a quarter (24.7%) of older adults was found to be multimorbid for chronic diseases (12). In another study from Nanjing, the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 60 publications
(63 reference statements)
5
19
1
1
Order By: Relevance
“…Some studies have identified hypertension as the most prevalent of the morbidities evaluated among individuals with higher BMI. 26,27,30 In addition, these results emphasize the findings of Guimarães et al, which indicate that weight control has a positive relationship with more suitable blood pressure measurements.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies have identified hypertension as the most prevalent of the morbidities evaluated among individuals with higher BMI. 26,27,30 In addition, these results emphasize the findings of Guimarães et al, which indicate that weight control has a positive relationship with more suitable blood pressure measurements.…”
Section: Discussionsupporting
confidence: 85%
“…A recent multicenter study showed that the average frequency of multimorbidity was 69.3% among elderly individuals, and these data were from medical wards of tertiary-care hospitals in China. In addition, this multicenter study showed that the prevalence of multimorbidity was higher in the northern area (71.7%), which was similar to our results, compared to the south (66%) 31 . In another survey conducted in eastern China, the prevalence of multimorbidity was 90.5% in the rural elderly population, which was higher than in our study 8 .…”
Section: Discussionsupporting
confidence: 91%
“…For example, Yang X et al (8) found that in 52 non-survivors with COVID-19, 22% had Type 2 Diabetes, while another study found that hypertension was the most common comorbidity reaching 30% in a sample of 191 patients (9). In recently published Chinese report, regarding an in-hospital sample of older persons (n=4,348) with a mean age of 74 years, found that hypertension was the most common comorbidity (63.1% prevalence) and increased to 72.5% in over 80 year olds from Wuhan (10). Indeed, both hypertension and Type 2 Diabetes were associated with a higher odds ratio of in-hospital death with COVID-19 (9).…”
Section: The Covid Spread In Italymentioning
confidence: 98%